QoS-based sensing scheduling protocol for wireless sensor networks - YAO Dao-yuan1; WANG Hai-lin 1; ZHANG Bao-xian2; LIU Hai-tao1 (Tongxin xuebao)
To satisfy the requirements of event detected latency according to different applications with unbalanced node density in randomly deployed large-scale wireless sensor networks,an adaptive distributed sensing scheduling protocol（ADSSP） which adaptively adjusts the duty cycles of sensor nodes based on node density and balances the energy consumption among sensor nodes was proposed.Compared with the random scheduling protocol,ADSSP can provide guaranteed lower average detection latency and also prolong the network lifetime up to 30 percent under the same situation.